Invasomes: An Artificial Vesicle Nanocarrier to Enhance Transdermal Drug Delivery - Preeti; Puri, Dinesh; Singh, Sanjay (Current Nanomedicine, 2024)
The greatest and most noticeable organ in the body is the skin. The stratum corneum, or top layer of skin, acts as a vital barrier to prevent skin penetration for many drugs. To overcome this barrier, numerous nanocarrier frameworks have been developed, which are important for the functioning of active agents. Vascular systems known as invasomes contain low levels of ethanol as well as terpenes or terpene combinations, which have a higher skin penetration rate and function as potential carriers. Improved drug delivery <span class=
Keywords: Terpenes